(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Emergency medical care for urgent conditions in children remains one of the most important and challenging areas of paediatrics. Children are a unique category of patients, as their physiological and anatomical characteristics, as well as their limited communication abilities, significantly complicate diagnosis and treatment in time-limited situations. Emergency conditions such as acute respiratory disorders, convulsive syndromes, trauma, infectious complications and anaphylaxis require a rapid and accurate response, which highlights the importance of developing and implementing modern approaches to care. Despite growing recognition of these needs, many children still receive emergency care in general emergency departments (GEDs) rather than in specialised paediatric emergency departments (SPEDs), often leading to poor outcomes due to a lack of specialised paediatric resources and training. This review describes the specific pathologies whicha are common in this area, diagnostic challenges encountered in newborns, infants, school-aged children, and adolescents, and evaluates existing patient triage systems and decision.